ASSESSMENT OF MICROBIOLOGICAL CONTAMINATION ON COMPUTER KEYBOARDS IN OFFICE SETTINGS: A CASE STUDY AT MADONNA UNIVERSITY, ELELE, RIVERS STATE, NIGERIA - JACK, Edidiong; Njoku, Samuel; Osuala, Oluchi; Edith Ijeego Mbah, Edith; Daokoru-Olukole, Chidinma; Onu, Euslar; Nwankwo, Grace; Okafor, Onyinyechi; Anagbaoso, Martin; Okonko, Iheanyi (Covenant Journal of Physical and Life Sciences, 2024)
Microorganisms inhabit various environments, displaying remarkable adaptability and proliferation capabilities. They colonize diverse surfaces, including those of computer keyboards, presenting potential health risks. This study investigates the prevalence of microbiological contamination on computer keyboards within office settings at Madonna University Nigeria, Elele, Rivers State, Nigeria. Swab samples were gathered and handled using standard microbiological techniques to distinguish between different types of bacteria and fungi. These microorganisms were then tested to see how they respond to commonly used antibiotics, and their genetic makeup was analyzed. The results showed the existence of harmful bacteria like Staphylococcus aureus, Bacillus cereus, Enterobacter sp, coagulase-negative Staphylococcus sp, Salmonella sp., and Escherichia coli. Various fungal species, such as Penicillium sp., Aspergillus sp., and Mucor sp. were also acknowledged. Antibiotic susceptibility tests indicated diverse resistance patterns among bacterial isolates, including multidrug resistance. Molecular characterization identified Bacillus cereus among the isolates. These findings underscore the potential health hazards associated with contaminated computer keyboards, emphasizing the importance of consistent cleaning and disinfection protocols to mitigate Malady transmission in shared environments.